2021
DOI: 10.1016/j.mprp.2020.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tool diameter ratio of tapered cylindrical profile pin on wear characteristics of friction stir processing of Al-Si alloy reinforced with SiC ceramic particles

Abstract: Friction stir processing is demonstrated to effectively enhance the surface and bulk properties of aluminum composites fabricated via the stir casting route. This process is performed below the melting point of the base material wherein common conventional fabrication problems such as solidification, liquidation cracking, and porosity are eliminated to a significant extent. Five different tools with varying tool diameter ratios are experimented on while maintaining tool rotational and traverse speeds and axial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…In the liquid state process, spray deposition, squeeze, and stir casting fabrication techniques are commonly utilised to produce MMCs.The fabrication methods of metal matrix composites play a very important role in the enhancement of mechanical properties. In conventional fabrication methods, problems such as poor wettability, uneven dispersion of particles, and porosity have been degrading the performance of MMCs [18][19][20][21][22]. Therefore, to avoid such issues and to attain homogeneous dispersion in the fabricated MMCs, squeeze casting technique can be preferred in this research.…”
Section: Introductionmentioning
confidence: 99%
“…In the liquid state process, spray deposition, squeeze, and stir casting fabrication techniques are commonly utilised to produce MMCs.The fabrication methods of metal matrix composites play a very important role in the enhancement of mechanical properties. In conventional fabrication methods, problems such as poor wettability, uneven dispersion of particles, and porosity have been degrading the performance of MMCs [18][19][20][21][22]. Therefore, to avoid such issues and to attain homogeneous dispersion in the fabricated MMCs, squeeze casting technique can be preferred in this research.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Vijayavel et al [28] used FSP to process the surface of the lm25 composite material with a volume fraction of 5% SiC. The experimental results showed that when the shaft-to-shoulder ratio of the stirring pin was 3.0, the obtained equiaxed grains were finer [29] and the microstructures processed at a tool traverse speed of 40 mm/min showed excellent wear resistance. Mohamadigangaraj et al [30] evaluated the effects of friction stir processing parameters on the properties of A390-10 wt% SiC composite using response surface methodology, and the results showed that the speed of rotation had a higher impact on hardness than other parameters.…”
Section: Introductionmentioning
confidence: 99%